Selection of Ground Motion Prediction Equations for the Global Earthquake Model. Issue 1 (February 2015) - Stewart, Jonathan P.; Douglas, John; Javanbarg, Mohammad; Bozorgnia, Yousef; Abrahamson, Norman A.; Boore, David M.; Campbell, Kenneth W.; Delavaud, Elise; Erdik, Mustafa; Stafford, Peter J.
Ground motion prediction equations (GMPEs) relate ground motion intensity measures to variables describing earthquake source, path, and site effects. From many available GMPEs, we select those models recommended for use in seismic hazard assessments in the Global Earthquake Model. We present a GMPE selection procedure that evaluates multidimensional ground motion trends (e.g., with respect to magnitude, distance, and structural period), examines functional forms, and evaluates published quantitative tests of GMPE performance against independent data. Our recommendations include: four models, based principally on simulations, for stable continental regions; three empirical models for interface and in-slab subduction zone events; and three empirical models for active shallow crustal regions. To approximately incorporate epistemic uncertainties, the selection process accounts for alternate representations of key GMPE attributes, such as the rate of distance attenuation, which are defensible from available data. Recommended models for each domain will change over time as additional GMPEs are developed.